Impaired Myocardial Perfusion from Persistent Mammary Side Branches: A Role for Functional Imaging and Embolization. (13th September 2010) - Firstenberg, Michael S.; Guy, Gregory; Bush, Charles; Raman, Subha V.
Abstract : The diagnosis and management of ischemic symptoms in patients after coronary artery bypass surgery can be challenging. It has been hypothesized that persistent branches of the internal mammary artery can divert flow from the left anterior descending artery and cause symptoms. We present a case in which successful coil embolization of a side branch improved flow and clinical symptoms. Side branch embolization might be a useful treatment option and should be considered in the management of symptomatic patients with a patent mammary graft.